Mechanistic and catalytic studies of β‐nitroalcohol crosslinking with polyamine. Issue 6 (8th October 2012) - Li, Xia; Li, Yongjun; Rao, Yi; Solomon, Marissa R.; Paik, David C.; Turro, Nicholas J.
Abstract β‐Nitroalcohols (βNAs) are promising corneoscleral crosslinking agents for the treatment of diseases such as keratoconus and myopia. Although it is believed that formaldehyde is released from the crosslinking reactions of βNAs, the mechanism by which βNAs react with amine‐functionalized polymers has yet to be known. In this study, we present the reaction mechanism of the βNA crosslinking. Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) data provide strong evidence that formaldehyde is released during the reaction. Catalytic studies show that sodium bicarbonate (NaHCO3) and salmon testes DNA accelerate the reaction while hydroxynitrile lyase from Arabidopsis thaliana decelerates the crosslinking reaction. These results suggest that βNAs are potential self‐administered crosslinking agents for future clinical use. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013